PENYEBAB REMAJA PUTUS SEKOLAH DUSUN I PULAU RAMBAI DI DESA PULAU RAMBAI KECAMATAN KAMPAR KABUPATEN KAMPAR - Nurul Fitri Hafifi; Titi Maemunaty; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the causes of teenagers dropping out of Dusun I Pulau Rambai Village in Rambai Island Kampa Kampar district. The formulation of the problem of this research is What are the internal and external causes as well as the dominant causes that caused the teenagers dropped out of Dusun I Pulau Rambai in the Village of Pulau Rambai Kampa Subdistrict Kampar District. The population in this study as many as 65 people drop out of school. The sampling technique used random sampling sampling technique. As stated by Sugiyono (2014: 120) the sampling of members of the population carried out randomly without regard to the strata in the polpulasi it. the formula used to determine the sample size is the Slovin formula (Bambang Prasetyo, 2005: 137). And 20 people for testing. The type of this research is descriptive with quantitative approach. The data collection instrument is questionnaire with 68 statements and after trial live 59 valid statement to be made in research instrument. Data analysis through quantitative descriptive analysis. The findings of this study indicate that internal causes have a percentage of 70.5% and external causes have a percentage of 66.9%, while the more dominant cause is external causes that has a percentage of 70.5%. Causes of Youth Dropout I Dusun Ramabai Island Village Village Rambai Kampa Kampar District Kampar, quite high with an average percentage of 68.7%.Keyword: Cause of drop out teenager